Cellular action of cholecystokinin-8S-mediated excitatory effects in the rat periaqueductal gray - Yang, Yu-Mi; Chung, Jun-Mo; Rhim, Hyewhon (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
The peptide cholecystokinin (CCK) is one of the major neurotransmitters modulating satiety, nociception, and anxiety behavior. Although many behavioral studies showing anti-analgesic and anxiogenic actions of CCK have been reported, less is known about its cellular action in the central nervous system (CNS). Therefore, we examined the action of CCK in rat dorsolateral periaqueductal gray (PAG) neurons using slice preparations and whole-cell patch-clamp recordings. Application of CCK-8S produced an inward current accompanied by increased spontaneous synaptic activities. The CCK-8S-induced inward current (I-CCK) was recovered after washout and reproduced by multiple exposures. Current-voltage plots revealed that I-CCK reversed near the equilibrium potential for K+ ions with a decreased membrane conductance. When several K+ channel blockers were used, application of CdCl2, TEA, or apamin significantly reduced I-CCK. I-CCK was also significantly reduced by the CCK2 receptor antagonist, L-365,260, while it was not affected by the CCK1 receptor antagonist, L-364,718. Furthermore, we examined the effects of CCK-8S on miniature excitatory postsynaptic currents (mEPSCs) in order to determine the mechanism of CCK-mediated increase on synaptic activities. We found that CCK-8S increased the frequency of mEPSCs, but had no effect on mEPSC amplitude. This presynaptic effect persisted in the presence of CdCl2 or Ca2+ -free bath solution, but was completely abolished by pre-treatment with BAPTA-AM, thapsigargin or L-365,260. Taken together, our results indicate that CCK can excite PAG neurons at both pre- and postsynaptic loci via the activation of CCK2 receptors. These effects may be important for the effects of CCK on behavior and autonomic function that are mediated via PAG neurons. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: NUCLEUS-TRACTUS-SOLITARIUS; MORPHINE ANALGESIA; OPIATE ANALGESIA; K+ CONDUCTANCE; CCKB RECEPTORS; B RECEPTORS; IN-VITRO; OCTAPEPTIDE; NEURONS; INVOLVEMENT